THE CIRCULAR ECONOMY IN THE FASHION INDUSTRY: IMPLICATIONS AND CHALLENGES FOR ITALIAN SMEs - Garcia Martin, Patricia Carolina (My University, 2016)
Current business practices and consumption patterns within the fashion industry have driven this sector towards the first positions in the ranking of most polluting economic systems. The situation has reached a point where mainstream sustainable practices cannot cope with the problem, leading the path to a new approach, the Circular Economy. This novel term aims to change the conception from recycling to reusing, closing the loop of economic systems transforming waste into inputs in a continuous circling of materials. The present document studies the implications of the Circular Economy from the perspective of the most representative companies in the fashion industry, small and medium enterprises. The objective is to answer the questions regarding how these companies integrate the Circular Economy in their supply chain management practices, and which challenges they encounter in the process. Thus, it comprises an explorative research aiming to provide the bases for the discovery of new knowledge on the matter. Data collection is based on semi-structured interviews with seven small and medium enterprises in Italy. Information is then analysed and contrasted with existing literature on the topic leading to reliable and valid answers to the questions. Findings show how there is a difference between the relevance of Circular Economy aspects depending on the nature of the closing loop. In other words, the integration of the approach is directly related with the nature of the companies’ resources, being these new or reused. At the same time, it also affects the challenges, originated within the upstream component of the chain for those organizations regenerating resources from other industries; whereas being the downstream component the main source of difficulties for those small and medium enterprises using new eco and bio resources.
Keywords: Circular Economy; Fashion Industry; Supply Chain Management; Small and Medium Enterprise; fi=Master's Degree Programme in International Business|